Sum 1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

Sum of consecutive positive integers

Question 1: Which integer can be expressed as a sum of (more than 1) positive integers?
Question 2: How to find out all the possible sums in Question 1?

1. First, by direct computation:

1 =? 11 =5+6
2 =? 12 =3+4+5
3 =1+2 13 =6+7
4 =? 14 =2+3+4+5
5 =2+3 15 =1+2+3+4+5=4+5+6=7+8
6 =1+2+3 16 =?
7 =3+4 17 =8+9
8 =? 18 =3+4+5+6
9 =4+5 19 = 9 + 10
10 =1+2+3+4 20 =2+3+4+5+6
It is easy to show that 1, 2, 4, 8, 16 can not be expressed as a sum of (more than 1) positive integers.
This leads to the following conjecture : An integer K can be expressed as a sum of (more than 1)
consecutive positive integers ⇔ K 6= 2m , where m is an integer. This conjecture can be proven
from the following:

2. Suppose a positive integer K = 2r s, where s ≥ 1 is odd and n > 1. Then K can be expressed as a
sum of n consecutive positive integers iff
1. n|2K

2. 2K > n(n − 1)

3. if n is even, then n = 2r+1 t for some t|s


1
Proof: If K = a + (a + 1) + · + (a + (n − 1)), then K = n(a + (a + (n − 1)))
2
1
1. K = n(2a + (n − 1)) ⇒ n(2a + (n − 1)) = 2K ⇒ n|2K
2

2. 2K = n(2a + (n − 1)) > n(n − 1)

2K 2r+1 s
3. if n is even, then = 2a + n − 1 is odd ⇒ is odd ⇒ n = 2r+1 t for some t|s
n n
µ ¶
1 2K
Conversely, if conditions 1, 2, and 3 are satisfied, then we can choose a = − (n − 1) .
2 n
Condition 2 guarantees that a > 0. Conditions 1 and 3 guarantee that a is an integer.
3. An integer K can be expressed as a sum of (more than 1) consecutive positive integers ⇔ K 6= 2m ,
where m is an integer.
Proof Suppose a positive integer K = 2m , where m is an integer and n > 1. If K can be expressed
as a sum of n consecutive positive integers, conditions 1 and 3 in the previous result imply that
n = 2m+1 ⇒ n(n − 1) = 2m+1 (2m+1 − 1) = 2K(2K − 1) ≥ 2K ⇒ condition 2 cannot be satisfied.
Therefore, integers of the form K = 2m cannot be expressed as a sum of consecutive positive
integers.
Conversely, suppose K 6= 2m . Then K = 2r s, where r ≥ 0 and s > 1 is odd. We only need to
consider the following 2 cases:

1. s > 2r+1 − 1 ⇒ n = 2r+1 satisfies conditions 1, 2 and 3. In this case,


s − (2r+1 − 1) s − (2r − 3) s−1 s+1 s + (2r+1 − 1)
K= + + ··· + + + ··· +
2 µ r+1 2 ¶ 2 2 2
2 −1+1 r+1
because RHS has 2 =2 terms, and first term + last term = s.
2
2r+1 s
Therefore, RHS = =K
r+1
2
2. s < 2µ + 1 ⇒ n¶= sµ satisfies conditions
¶ 1, 2 and 3.
µ In this case,

r s−1 r s−3 r r s−1
K= 2 − + 2 − + ··· + 2 + ··· 2 +
2 µ ¶ 2 2
s−1
because RHS has 2 + 1 = s terms, and first term + last term = 2r+1 .
2
s2r+1
Therefore, RHS = =K
2
4. Example:
9−7 9+7
1 K = 36 = 22 9, 9 > 22+1 − 1 = 7, = 1, =8
2 2
⇒ 36 = 1 + 2 + 3 + · · · + 8

3−1 3−1
2 K = 48 = 24 3, 3 < 22+1 + 1 = 9, 24 − = 15, 24 + = 17
2 2
⇒ 48 = 15 + 16 + 17

3. K = 60, n satisfies conditions 1, 2 and 3 in 2 ⇔ n = 3, 5, 8 which correspond to


60 = 19+20+21 = 10+11+12+13+14 = 4+5+6+7+8+9+10+11
5. The above problem can be rephrased as follows: Which number can be written as the sum of
consecutive terms from the sequence

1, 2, 3, 4, 5, 6, 7, · · ·

Replacing the above sequence by a different one, we get a different problem. For example, if we
replace the sequence with
1, 3, 5, 7, · · ·
we have the following

6. Which number can be written as the sum of consecutive odd positive integers?

7. Again, we can start with some specific calculation:

1 =? 11 =? 21 =5+7+9
2 =? 12 =5+7 22 =?
3 =? 13 =? 23 =?
4 =1+3 14 =? 24 = 3 + 5 + 7 + 9 = 11 + 13
5 =? 15 =3+5+7 25 =1+3+5+7+9
6 =? 16 =1+3+5+7 26 =?
7 =? 17 =? 27 = 7 + 9 + 11
8 =3+5 18 =? 28 = 13 + 15
9 =1+3+5 19 =? 29 =?
10 =? 20 = 9 + 11 30 =?

8. A positive integer n can be written as the sum of consecutive odd positive integers iff n is an odd
composite number or 4|n.

Proof: ” ⇒ ” Suppose n = (2x + 1) + (2x + 3) + · · · + (2y − 1), where y > x + 1. Then


n = y 2 − x2 = (y + x)(y − x). If x and y are of the same parity, then both (y + x) and y − x are
even and 4|n. If x and y are of different parities, then n is odd and composite.
” ⇐ ” If n is an odd composite number or 4|n, then we can write n = pq, where p ≥ q > 1 and p,
p+q p−q
q are of the same parity. Therefore, putting y = and x = ,we have y − x = q > 1 and
2 2
n = (y + x)(y − x) = y 2 − x2 = (2x + 1) + (2x + 3) + · · · + (2y − 1).

You might also like